The Pollock-Krasner Foundation, Inc. : Tenth Anniversary Report 1985-1995. - Bergman, Charles C.; Thaw, Eugene Victor (New York : The Pollock-Krasner Foundation Inc., 1995)
Boardman, Seymour ; Lazarevic, Milo ; Daphnis, Nassos ; Kirk, Jonathan ; Maury, Richard ; Martin, Susan ; Williamson, Philomena ; Bills, tom ; Gechtoff, Sonia ; Gordon, Mark ; Stefanelli, Joe ; Vail, Clover ; Robinson, Bob ; Szikora, Tamás ; Burns, Maurice ; Jagdish, Chinthala ; Thurston, Steven Mark ; Blow, Sandra ; Leighton, Patricia ; Ocampo, Manuel ; MacIver, Loren ; Frank, Mary ; Jaffé, Shirley ; Dugmore, Edward ; Lassau, Ibram ; Waitzkin, Stella
Engels
boek